FACTORS THAT LEAD TO THE EFFICIENT MANAGEMENT OF THE MATERIAL SUPPLY CHAINS OF OIL AND GAS INDUSTRIES IN INDONESIA (Journal of Technology and Operations Management, 2015)
The supply chains management in oil and gas industries is currently facing problems regarding its flows of materials. The basic theory of supply materials has not been well practiced to support its operational processes. Inefficiency of supply chains and logistics practices will reduce the performance of oil and gas industries. Therefore, this study aims to investigate the relationship between external factors of material supply and logistics performance (dependent variable) and three (3) factors related to independent variables. The three (3) factors (independent variables) representing to the external of materials supply which includes the infrastructure technology, transport policy & regulation and transport availability. A survey was conducted among the practitioners of oil and gas industries and the total of 108 respondents were accepted and analyzed. The Statistical Package for Social Sciences (SPSS) (version 18) and the related statistical techniques were also used. The findings of this study indicated that there were significant relationships for better ways in dealing with material supply and logistics towards the efficiencies for oil and gas industries in Indonesia. The findings are also suggested to be used in future guidelines for the related industries.